Underpricing and market timing in SEOs of European REITs and REOCs. Issue 3 (16th December 2019) - Lorenz, Felix
Abstract : Purpose: The purpose of this paper is to contribute to the literature on seasoned equity offerings (SEOs) by examining the underpricing of European real estate corporations and identifying determinants explaining the phenomenon of setting the offer price at a discount at SEOs. Design/methodology/approach: With a sample of 470 SEOs of European real estate investment trusts (REITs) and real estate operating companies (REOCs) from 2004 to 2018, multivariate regression models are applied to test for theories on the pricing of SEOs. This paper furthermore tests for differences in underpricing for REITs and REOCs as well as specialized and diversified property companies. Findings: Significant underpricing of 3.06 percent is found, with REITs (1.90 percent) being statistically less underpriced than REOCs (5.08 percent). The findings support the market timing theory by showing that managers trying to time the equity market gain from lower underpricing. Furthermore, underwritten offerings are more underpriced to reduce the risk of the arranging bank, but top-tier underwriters are able to reduce offer price discounts by being more successful in attracting investors. The results cannot support the value uncertainty hypothesis, but they are in line with placement cost stories. In addition, specialized property companies are subject to lower underpricing. Practical implications: An optimal issuance strategy taking into account timing, relative offer size and the choice of the underwriter can minimize the amount of "money left on the table" and therefore contribute to the lower cost of raising capital. Originality/value: This is the first study to investigate SEO underpricing for European real estate corporations, pricing differences of REITs and REOCs in seasoned offerings and the effect of market timing on the pricing of SEOs.